Straddling multiple streams: focusing events, policy entrepreneurs and problem brokers in the governance of English fire and rescue services - Peter Eckersley; Katarzyna Lakoma (Policy Studies, 2021)
Empirical studies that use the multiple streams approach often examine cases of reactive policymaking in response to "focusing events", rather than proactive policymakers who seek to broker or construct problems that their preferred solution might address. Drawing on publicly-available debates about reforms to fire and rescue services in seven areas of England, we show how individuals within small policy subsystems may construct problems to try and convince others to support their preferred policy solution. By straddling all three streams and acting as endogenous policy entrepreneurs, policymakers and problem brokers simultaneously, we highlight how these actors can exert substantial influence over policymaking processes – although consensus within the political stream about the existence of a genuine problem is still a key factor in facilitating change. These insights allow us to introduce a more obvious power dimension and greater predictive capacity into the multiple streams approach.
Keywords: 320; Multiple streams; focusing events; policy entrepreneurs; problem brokers; fire and rescue services; police forces; England